2021
DOI: 10.1109/jphot.2021.3094646
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Grating Couplers for the Optical Addressing of Trapped Ions

Abstract: In this work, silicon photonics structures for the optical addressing of trapped ion is developed for quantum computing applications. Grating-waveguide-grating structures of various designs are designed, and fabricated for various radius curvatures of 12, 15, 25 and 30 µm, respectively. From the optical measurements, gratings with radius of curvature of 25 and 30 µm exhibit lower power loss of 36.5 and 33.9 dB with better-focused beam profiles as compared to those with radius of curvature of 12 and 15 µm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…6(c) and (d), the beam waist along y-axis do not show significant difference between fixed pitch grating and mixed pitch gratings. As the beam waist along y-axis mainly depend on the taper shape and the radius of curvature [25], mixing the pitch in the grating shall not have direct influence towards the beam waist along y-axis. Whereas for beam waist along x-axis, it is observed that 6(1.2µm), 5(1.2µm), and 4(1.2µm) mixed pitch gratings show lower beam waists (Fig.…”
Section: 𝑚𝑚mentioning
confidence: 99%
“…6(c) and (d), the beam waist along y-axis do not show significant difference between fixed pitch grating and mixed pitch gratings. As the beam waist along y-axis mainly depend on the taper shape and the radius of curvature [25], mixing the pitch in the grating shall not have direct influence towards the beam waist along y-axis. Whereas for beam waist along x-axis, it is observed that 6(1.2µm), 5(1.2µm), and 4(1.2µm) mixed pitch gratings show lower beam waists (Fig.…”
Section: 𝑚𝑚mentioning
confidence: 99%
“…[20][21][22] Furthermore, integrated photonic control with 2D focusing surface grating couplers (GCs) has been used to diffract guided light from the chip to the ions captured in free space. [23][24][25] Full coherent control of a single trapped ion qubit has since been reported; a chip with four GCs designed for four wavelengths demonstrated fully integrated ion trapping, laser cooling, qubit initialization, and state control. 26,27) However, for multi-qubit control, tightly focused irradiation is needed for ions in a tightly packed chain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in our previous work, we reported the investigation on the focusing of grating coupler with various radius of curvatures (r) on Silicon-On-Insulator (SOI) platform. Beam focusing along the out-of-plane axis has been observed [8]. However, the focusing was demonstrated on 1630 nm wavelength on silicon-on-insulator (SOI) platform, which is not applicable for optical addressing of trapped ions.…”
mentioning
confidence: 99%
“…It has been reported that SOI platform is suitable for silicon photonics at near-to mid-infrared (NIR and MIR) range, due to the high transmissivity of silicon for NIR to MIR light (∼1200 nm onwards) [9]. Thus, the SOI is selected for grating design under 1630 nm wavelength in our previous study [8]. In the case of 1092 nm, SiN platform is selected due to the high transmissivity of SiN for visible and NIR range, which covers the wavelength-of-interest in this study [10].…”
mentioning
confidence: 99%